Learning Stencyl 3.x game development beginner's guide : a fast-paced, hands-on guide for developing a feature-complete video game on almost any desktop computer, without writing a single line of computer code /: a fast-paced, hands-on guide for developing a feature-complete video game on almost any desktop computer, without writing a single line of computer code. (2013) - Unknown
No abstract available